Penguin puzzle - Stamper, Judith Bauer; Enik, Ted. (New York : Scholastic, 2001)
Miss Frizzle's class travel to Antarctica to learn about penguins.
"Based on the magic school bus books written by Joanna Cole and illustrated by Bruce Degan"--T.p. verso.
510
Accelerated Reader AR
Keywords: Penguins -- Fiction; Antarctica -- Fiction